Prevalence and correlates of hyperglycemia in a rural population, Vietnam: implications from a cross-sectional study - Quang Binh Tran; Tran Phuong Pham; Thi Nhung Bui; Dinh Thoang Dang; Van Thang Pham; Khanh Long Tran; Van Thanh Duong (BMC, 2012)
Abstract Background Despite the increasing prevalence of type 2 diabetes in urban areas, relatively little has been known about its actual prevalence and its associations in rural areas, Vietnam. The purpose of this study was to evaluate the prevalence of impaired fasting glucose (IFG), impaired glucose tolerance (IGT), diabetes and their risk factors in a rural province, Vietnam. Methods A cross-sectional study with a representative sample was designed to estimate the hyperglycemia prevalence, using 75-g oral glucose tolerance test. Potential risk factors for hyperglycemia were analyzed using multinomial logistic regression, taken into account influences of socio-economic status, anthropometric measures, and lifestyle-related factors. Results The age and sex-adjusted prevalence rates (95% CI) of isolated IFG, isolated IGT, combined IFG-IGT, and diabetes were 8.7 (7.0-10.5), 4.3 (3.2−5.4), 1.6 (0.9−2.3), and 3.7% (2.7-4.7%), respectively. There were still 73% of diabetic subjects without knowing the condition. Blood pressure, family history of diabetes, obesity-related measures (waist circumference, waist-hip ratio, body fat percentage, and abdominal obesity) were the independent risk factors for hyperglycemia (IFG, IGT, and diabetes). Conclusions The prevalence of hyperglycemia in rural areas has not been as sharply increased as that reported in urban cities, Vietnam. Blood pressure and obesity-related measures were the most significant predictors for hyperglycemia level and they can be taken into account in building prognosis models to early detection of diabetes in rural Vietnamese populations.